1996
DOI: 10.1346/ccmn.1996.0440212
|View full text |Cite
|
Sign up to set email alerts
|

Exchange Reactions in the Ca-Mg-Na-Montmorillonite System

Abstract: Abstract--The exchange reactions of Na, Ca and Mg on montmorillonite are revisited employing recently developed analytical and theoretical approaches. The fractional adsorption of the cations has been determined by displacing them from the adsorbed state in one step, using a low concentration of an organic cation of large binding affinity. The analysis of displaced and solution cations employed inductively coupled plasma emission spectrometry. An adsorption model was employed in the analysis of the data. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 28 publications
2
45
0
Order By: Relevance
“…The results were analyzed with the adsorption model (Nir 1986;Nir et al 1986;Hirsch et al 1989;Rytwo et al 1996) by using binding coefficients from previous studies (given in Table 1). The calculations con- (Rytwo et al 1996 and the current work); Cd (10 M -l) and CdCI + (30 M -I) as in Hirsch et al (1989); Na (0.5 M-~), K (4 M 1) as in Nir et al (1986).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results were analyzed with the adsorption model (Nir 1986;Nir et al 1986;Hirsch et al 1989;Rytwo et al 1996) by using binding coefficients from previous studies (given in Table 1). The calculations con- (Rytwo et al 1996 and the current work); Cd (10 M -l) and CdCI + (30 M -I) as in Hirsch et al (1989); Na (0.5 M-~), K (4 M 1) as in Nir et al (1986).…”
Section: Resultsmentioning
confidence: 99%
“…The calculations con- (Rytwo et al 1996 and the current work); Cd (10 M -l) and CdCI + (30 M -I) as in Hirsch et al (1989); Na (0.5 M-~), K (4 M 1) as in Nir et al (1986). The total concentrations in the system (clay + solution) were 2.52 mM for Ca, 0.479 mM for Mg, 0.048 mM for K and 10.13 mM for Na.…”
Section: Resultsmentioning
confidence: 99%
“…This process was repeated three times. The cation-saturated montmorillonite was then washed three or four times with distilled water until the AgNO 3 test for chloride became negative [18,19].…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that kimberlite is prone to weathering when smectite minerals are present [2] and that weathering correlates with the abundance of smectite. Cation exchange takes place in smectites and changes the mechanical properties of the kimberlite [3], [4], [5] and [6]. K + is one of the few cations that collapse the swelling clay interlayer of smectites [7], [8] and [9].…”
Section: Introductionmentioning
confidence: 99%